1997
DOI: 10.1073/pnas.94.12.6335
|View full text |Cite
|
Sign up to set email alerts
|

The epitopes for natural polyreactive antibodies are rich in proline

Abstract: ABSTRACT''Natural'' polyreactive antibodies, which bind in a nonspecific manner to a range of biological molecules both of self-and nonself-origin, are normal constituents of serum and are a significant part of the immune repertoire in many species, including humans. Autoantibodies to sTNF-R (the 55-kDa extracellular domain of the human receptor to tumor necrosis factor ␣) were affinity purified from normal human sera using immobilized sTNF-R. The isolated antisTNF-R IgG bound both native and denatured forms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 36 publications
1
25
1
Order By: Relevance
“…In addition, truncated PspA fragments containing the ␣-helical domain of the molecule, the clade-defining region, and the proline-rich repeat region show increased cross-protective capabilities over fragments containing the ␣-helical domain and clade-defining region alone (31). Human sera often contain natural, polyreactive antibodies that recognize prolinerich epitopes; these antibodies may represent early defense mechanisms against pathogens (35). Together, these data suggest that exposed proline-rich regions of surface antigens may represent pathogen-associated molecular patterns that are recognized by the immune system (24).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, truncated PspA fragments containing the ␣-helical domain of the molecule, the clade-defining region, and the proline-rich repeat region show increased cross-protective capabilities over fragments containing the ␣-helical domain and clade-defining region alone (31). Human sera often contain natural, polyreactive antibodies that recognize prolinerich epitopes; these antibodies may represent early defense mechanisms against pathogens (35). Together, these data suggest that exposed proline-rich regions of surface antigens may represent pathogen-associated molecular patterns that are recognized by the immune system (24).…”
Section: Discussionmentioning
confidence: 99%
“…As many innate defence mechanisms rely on the recognition of structures shared by large groups of parasites, they are regarded as rather unspecific, that is the defence does not distinguish between different parasite genotypes (Kurtz 2005). However, the innate immune system also possesses recognition mechanisms able to differentiate between different antigens, involving for example, natural antibodies, Toll and lectin-like receptors (Tchernychev et al 1997;Kurtz 2005; for fish innate immune system see Magnadóttir 2006). Note that a genotype specific host defence alone will not produce, but is a prerequisite, for genotype by genotype host-parasite interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, peptides containing proline repeats usually exist on the surface of the protein structure. The peptide structure with proline repeats can consequently serve as a conformation-dependent common "public" epitope for natural antibodies (Tchernychev et al, 1997). Examination of the specificity of the rabbit polyclonal antibody raised to full-length SULT2B1b demonstrated that, when used for immunoblot analysis, this antibody readily detected full-length SULT2B1b but did not immunoreact with truncated SULT2B1b.…”
Section: Discussionmentioning
confidence: 99%
“…In proteins, proline generally occurs at solvent-exposed sites such as in loops, turns, N-terminal first turn of helix, and random coils (Tchernychev et al, 1997). Therefore, peptides containing proline repeats usually exist on the surface of the protein structure.…”
Section: Discussionmentioning
confidence: 99%